If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 42 = 9x + -2 Reorder the terms: 42 + 5x = 9x + -2 Reorder the terms: 42 + 5x = -2 + 9x Solving 42 + 5x = -2 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 42 + 5x + -9x = -2 + 9x + -9x Combine like terms: 5x + -9x = -4x 42 + -4x = -2 + 9x + -9x Combine like terms: 9x + -9x = 0 42 + -4x = -2 + 0 42 + -4x = -2 Add '-42' to each side of the equation. 42 + -42 + -4x = -2 + -42 Combine like terms: 42 + -42 = 0 0 + -4x = -2 + -42 -4x = -2 + -42 Combine like terms: -2 + -42 = -44 -4x = -44 Divide each side by '-4'. x = 11 Simplifying x = 11
| 4x-8=21 | | 16w+12=60 | | 2(x+3)-4x=40 | | 7(x+2)=3(x+12) | | 6(x-2)-7(x-4)=6-3x | | 6(x-2)-7(x-4)=6-3 | | 6x+4=13+5x | | -5x-8x=26 | | -3b+b=10 | | -b+b=10 | | 3x+5=2+6x | | 5x+3x-5=3 | | 4logx=8 | | ln(x^2)-2lnx=0 | | 2x*(x-4y)= | | cos(0.5x)=0.5 | | t^3-12t^2+36t-30=0 | | 12c+12y=36 | | 0.4+42= | | 42-6x=24 | | P=2c+xforc | | 227=146v | | log(3)(6x-2)=4 | | 7-4(w-2)w= | | 2y+y=25 | | 2x+4y+0.25z=100solve | | 6m=1500 | | 0.5x+402=5.9 | | 14y^3+8y^2+7y+4=0 | | 180*y+4050*x=22000 | | 4050*x+180*y=22000 | | 5n+3n=-2(1-7n) |